TLR7 Agonism Accelerates Disease and Causes a Fatal Myeloproliferative Disorder in NZM 2410 Lupus Mice - Wirth, Jena R.; Molano, Ivan; Ruiz, Phil; Coutermarsh-Ott, Sheryl; Cunningham, Melissa A. (Frontiers in Immunology, 2020)
Murine models of lupus, both spontaneous and inducible, are valuable instruments to study SLE pathogenesis. Accelerants such as Type I IFN are often used to trigger earlier disease onset. We used a topical TLR7 agonist, previously reported to induce lupus-like disease in WT mice within weeks, to validate this data in C57BL/6j mice, and to test TLR7 agonism as an accelerant in lupus-prone NZM2410 mice. We found that TLR7-stimulated B6 and NZM2410 mice had significantly reduced survival and exhibited profound splenomegaly with significantly reduced B cells (4% vs. 40%), and T cells (8% vs. 31%). Spleen pathology and IHC revealed massive expansion of F4/80+ cells in TLR7-treated mice consistent with histiocytosis. While resiqimod treatment caused mild autoimmunity in B6 mice and accelerated autoimmunity in NZM2410 mice, it did not cause significant nephritis or proteinuria in either strain (renal function intact at death). Given the macrophage expansion, cytopenias, and disruption of normal splenic lymphoid follicle architecture, histiocytic sarcoma is favored as the cause of death. An alternative etiology is a macrophage activation syndrome (MAS)-like syndrome, since the mice also had a transaminitis and histologic hemophagocytosis in the setting of their rapid mortality. For investigators who are focused on murine models of lupus nephritis, this model is not ideal when utilizing B6 mice, however topical resiqimod may prove useful to accelerate autoimmunity and nephritis in NZM2410 mice, or potentially to investigate secondary complications of lupus such as histiocytic diseases or macrophage activation like syndromes.